Renovating on Unequal Premises: A Normative Framework for a Just Renovation Wave in Swedish Multifamily Housing - Jenny von Platten; Karl de Fine Licht; Mikael Mangold; Kristina Mjörnell (Energies, 2021)
While the energy transition of the EU housing stock is now being intensified with the launch of the Renovation Wave, economic inequalities are increasing in many OECD countries, which has effects on housing-related inequalities and the demand of affordable housing. The Renovation Wave is thus an opportunity to improve housing quality for low-income households, but also entails risks for increased rents. In Sweden, the standard of housing is relatively high and energy poverty in multifamily housing is rare, meaning that there are limited social benefits to be achieved from extensive energy retrofitting; moreover, Sweden lacks a social housing sector, which limits protection of the worst-off residents. This paper thus explores whether the limited social benefits of the Renovation Wave weigh up against the risks that it entails for the worst-off in the Swedish context. This is done within a normative framework for just energy transitioning that is developed within the context of the Renovation Wave and increasing economic inequalities, consisting of four ordered principles: (1) The equal treatment principle; (2) The priority principle; (3) The efficiency principle; and (4) The principle of procedural fairness. Analysis showed that to be considered just according to our framework, the Swedish energy transition of housing should, in contradistinction to what is suggested in the Renovation Wave, limit the imposition of extensive energy retrofitting in low-income areas. Finally, having identified a mismatch between the most effective approaches in terms of energy savings and the most acceptable approaches in terms of social justice, we offer policy recommendations on how to bridge this mismatch in a Swedish context.